THINKING ABOUT THE END OF LIFE WHEN IT IS NEAR: A COMPARISON OF GERMAN AND PORTUGUESE CENTENARIANS. (11th November 2018) - Jopp, D; Boerner, K; Kim, K; Butt, A; Ribeiro, O; Araujo, L; Rott, C
Abstract: Centenarians approach the end of their lives with certainty. Yet, little is known about their thoughts about the end of life (EOL). Comparing centenarians from Germany and Portugal, this study examined common thinking of and planning for the EOL among centenarians, and whether views on EOL are shaped by cultural contexts and individual characteristics. Centenarians from two larger population-based centenarian studies (87 German and 128 Portuguese) responded to five questions regarding their views on EOL. Using Latent Class Analyses, we identified patterns of EOL thoughts and examined differences in country and individual characteristics by the derived patterns. A significant portion of centenarians in both countries reported not thinking about the EOL, not believing in the afterlife, and not having made EOL arrangements; perceiving the EOL as threatening and longing for death were less commonly endorsed. LCA identified three latent patterns of EOL thoughts: Class 1 (EOL thoughts, EOL arrangements, and afterlife beliefs); Class 2 (EOL arrangements and afterlife beliefs); and Class 3 (overall low). The proportion of Portuguese centenarians was higher in Class 1, whereas the proportion of German centenarians was higher in Class 2 and 3. Class membership was also related to centenarians' demographic, social, and health characteristics. In sum, findings indicate that despite closeness to death, centenarians do not necessarily think about and/or prepare for the EOL. Given that lack of EOL planning can result in poorer EOL quality, enhancing communication among centenarians, family, and health care professionals seems imperative.